Fruit consumption and multiple health outcomes: An umbrella review. (December 2021) - Sun, Liuqiao; Liang, Xiaoping; Wang, Yaoyao; Zhu, Sui; Ou, Qian; Xu, Hang; Li, Fangyuan; Tan, Xuying; Lai, Zhiwei; Pu, Liuzhen; Chen, Xingyi; Wei, Jun; et al.
Abstract: Background: Although several systematic reviews and meta-analyses have been conducted to assess the relationship between fruit intake and health outcomes, the results of the relationship are inconclusive. Scope and approach: We conducted an umbrella evaluation of existing research on the relationship between fruit intake and various health outcomes in humans. We used A Measurement Tool to Assess Systematic Reviews 2 and Grade of Recommendations, Assessment, Development and Evaluation to comprehensively evaluate the methodological quality and evidence quality of the research. We also performed a subgroup analysis based on the study design. Key findings and conclusions: The umbrella review covered 59 qualified studies, which included 77 meta-analyses and 66 health outcomes. No adverse relationships between fruit intake and health outcomes were found. Moderate-quality evidence suggested that one serving increment of fruit per day could decrease the risks of cardiovascular disease (RR: 0.97, 95% CI: 0.95 to 0.99), stroke (RR: 0.92, 95% CI: 0.88 to 0.96), coronary heart disease (RR: 0.96, 95% CI: 0.93 to 0.99), and oral cancer (OR: 0.51, 95% CI: 0.40 to 0.65). And moderate-quality evidence presented that 200 g increment of fruit intake per day was associated with lower risk of breast cancer (RR: 0.94, 95% CI: 0.89 to 0.99), and the risk of type 2 diabetes mellitus could be reduced by 8%-12% when the fruit intake increasing to 100-500 g/d. For the remaining studies, the quality of evidence was either low or very low. We also found that the study design could influence the significance of the association between fruit intake and health outcomes. Large-sample, multi-center, and multi-country randomized controlled trials or prospective studies are required to verify our results. Highlights: Umbrella review was conducted to evaluate the relationship between fruit intake and multiple health outcomes. Increasing the fruit intake by 1 serving/d could reduce the risks of CVD, stroke, CHD and oral cancer by 3%, 8%, 4% and 49%. Increasing the fruit intake by 200 g/d could reduce the risk of breast cancer by 6%. Increasing the fruit intake to 100–500 g/d could reduce the risk of type 2 diabetes mellitus by 8%–12%.